Influence of Post-Core and Crown Type on the Fracture Resistance of Incisors Submitted to Quasistatic Loading - Uctasli Sadullah; Boz Yakup; Sungur Sercan; Vallittu Pekka K; Garoushi Sufuan; Lassila Lippo (Switzerland, 2022)
The aim of this paper was to evaluate the fracture resistance and failure type of maxillary incisor teeth, rebuilt with various types of post-core restorations and full crowns made of either direct conventional particulate filler composite (PFC, G-aenial Anterior, GC, Tokyo, Japan) or indirect CAD/CAM restorations (composite Cerasmart 270 and glass ceramic LiSi Block from GC). One hundred (n = 10/group) central incisors were cut and divided into 10 experimental groups restored with different approaches. In approach A, teeth were restored with a core build-up composite (Gradia Core, GC) for a core and full crown of PFC. Approach B had teeth restored using composite core and prefabricated fiber posts, and a complete crown of either PFC or CAD/CAM. Approach C contained teeth restored with a core of short fiber-reinforced composite (everX Flow, GC) and prefabricated fiber posts, and a complete crown of either PFC or CAD/CAM. In approach D, the teeth had a core of short fiber-reinforced composite only, and a complete crown of either PFC or CAD/CAM restorations. The root canals were prepared, and when posts were used, they were luted with either a dual-cure resin cement (LinkForce, GC) or everX Flow. As the control, sound teeth (n = 10) were used. Restorations were quasi-statically loaded until fracture. Failure type was visually investigated. The interface between the fiber post and luting cement was investigated using SEM, before and after completion of the loading test. The data were analyzed by analysis of variance (p = 0.05) followed by Tukey's test. None of the restorative approaches restored the fracture load strength of intact teeth (p < 0.05). Restorations with additional fiber posts (Approaches B and C) had higher load-bearing capacity (p < 0.05) than restorations without fiber posts (Approaches A and D). Restorations that had short fiber-reinforced composite cores with or without fiber posts presented more repairable failures. Using short fiber-reinforced composite as post-luting and core build-up material with conventional fiber posts proved to be a promising method to strengthen severely damaged incisors.